The Nonfiction Comic as a Source for the Study of Armed Conflicts: Chronicles of Jerusalem [el Cómic de No-Ficción Como Fuente Para el Estudio de Los Conflictos Bélicos: Crónicas de Jerusalén] - Sola-Morales, S (Universidad Complutense de Madrid, 2014)
This paper questions which contributions can have a comic, as an hybrid genre, on the historical research of the Arab-Israeli conflict. Specifically, we analyze the discourse and the historical content of the comic book Jerusalem: Chronicles from the Holy City, by Guy Delisle, in relation to three topics: first, the configuration of the context of reference and the pretense of neutrality; second, the use of sources and the construction of the story; and third, the prospective of the conflict. The main conclusion we have reached is that this non-fiction comic is a very useful complementary source for historical research and comprehension of this conflict that still no have solution.